If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = -6f Solving -24 = -6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '6f' to each side of the equation. -24 + 6f = -6f + 6f Combine like terms: -6f + 6f = 0 -24 + 6f = 0 Add '24' to each side of the equation. -24 + 24 + 6f = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 6f = 0 + 24 6f = 0 + 24 Combine like terms: 0 + 24 = 24 6f = 24 Divide each side by '6'. f = 4 Simplifying f = 4
| (9*10^6)1/2 | | 3(x+3)+6=5x-2(-5+x) | | y-5=-8(x+2) | | y+40=-8x+2 | | y+5=-8(x-2) | | b-6a=-3for*b | | -4x+24-4x^2=0 | | y+40=-8(x+2) | | 2.31/.10 | | (2x^3-5x^2+3x)-(6x^2+2x+6)= | | 5x-3(1+x)=2(-7+x-1)-7 | | 5x-3=3(x+1)+2-6 | | (2x^3-5x^2+3x)-6x^2+2x+6= | | Lnx=-10.34 | | 3w+30=-2(w-5) | | 9^2-3x=1/81 | | 6(4x-1)/5(x-3)= | | 4a^2+64=0 | | 9x-6=9(x-4) | | b-6a=-3forb | | 0.02(y-8)+0.06y=0.18y-0.01(40) | | (1/4)^4x-6=64 | | -3w+3=-10w+30 | | .5(16n-12)=9n+11 | | x^3-4x^2+6x-3=0 | | -2=x-1 | | 6x+35=-66+2.5(36x)+2 | | (14xy^2)^(1/3) | | (14xy^2)^(1/2) | | 9x^2=26x+80 | | 10000x+34000=2000x+88000 | | y=2x^3+6 |